Using molecular docking to investigate the anti-breast cancer activity of low molecular weight compounds present on wild mushrooms. - Froufe, Hugo J.C. (2011)
Mushrooms represent an unlimited source of compounds with antitumor and immunostimulating properties and mushroom intake as been shown to reduce the risk of breast cancer. A large number of LMW (low molecular weight) compounds present in mushrooms have been identified including: phenolic acids, flavonoids, tocopherols, carotenoids, sugars and fatty acids. In order to evaluate which wild mushroom LMW compounds may be involved in anti-breast cancer activity we selected a representative dataset of 43 LMW compounds and performed molecular docking against 3 known protein targets involved in breast cancer (Aromatase, Estrone Sulfatase and 17β-HSD-1) using AutoDock4 as docking software. The estimated inhibition constants for all LMW compounds were determined and the potential structure-activity relationships for the compounds with the best estimated inhibition constants are discussed for each compound family. 4-O-caffeoylquinic, naringin and lycopene stand out as the top ranked potential inhibitors for Aromatase, Estrone Sulfatase and 17β-HSD1, respectively, and the 3-D docked conformation for these compounds are discussed in detail. This information provides several interesting starting points for further development of Aromatase, Estrone Sulfatase and 17β-HSD1 inhibitors.